The Relationship Between the Duration of Attention to Pandemic News and Depression During the Outbreak of Coronavirus Disease 2019: The Roles of Risk Perception and Future Time Perspective - Wu, Lanting; Li, Xiaobao; Lyu, Hochao (Frontiers in Psychology, 2021)
Since the outbreak of COVID-19 in China, people have been exposed to a flood of media news related to the pandemic every day. Studies have shown that media news about public crisis events have a significant impact on individuals’ depression. However, how and when the duration of attention to pandemic news predicts depression still remains an open question. This study established a moderated mediating model to investigate the relationship between duration of attention to pandemic news and depression, the mediating effect of risk perception and the moderating effect of future time perspective on the relationship. In early February 2020, 701 individuals from 29 provinces, autonomous regions and municipalities across China were asked to self-report their duration of attention to pandemic news, level of depression, risk perception, and future time perspective during the COVID-19 outbreak. Results show that there is a significant positive correlation between duration of attention to news on COVID-19 and depression; risk perception mediates the association between duration of attention to pandemic news and depression; and future time perspective plays a moderating role between risk perception and depression. The findings of the present study provide theoretical implications and practically throw some light on alleviating the public’s depression during pandemic periods. We highlight that the individual’s hope for a better future, focusing positive news and time perspective balance during epidemic disease are also beneficial to promoting positive emotion and reducing the depression.